Sevoflurane based anaesthesia does not affect already impaired cerebral autoregulation in patients with type 2 diabetes mellitus. (December 2018) - Sperna Weiland, N.H.; Hermanides, J.; van der Ster, B.J.P.; Hollmann, M.W.; Preckel, B.; Stok, W.J.; van Lieshout, J.J.; Immink, R.V.
Abstract: Background: The baroreflex regulates arterial blood pressure (BP). During periods when blood pressure changes, cerebral blood flow (CBF) is kept constant by cerebral autoregulation (CA). In patients with diabetes mellitus (DM), low baroreflex sensitivity (BRS) is associated with impaired CA. As sevoflurane-based anaesthesia obliterates BRS, we hypothesised that this could aggravate the already impaired CA in patients with DM resulting in a 'double-hit' on cerebral perfusion leading to increased fluctuations in blood pressure and cerebral perfusion. Methods: On the day before surgery, we measured CBF velocity (CBFV), heart rate, and BP to determine BRS and CA efficacy (CBFVmean -to-BPmean -phase lead) in 25 patients with DM and in 14 controls. During the operation, BRS and CA efficacy were determined during sevoflurane-based anaesthesia. Patients with DM were divided into a group with high BRS (DMBRS↑ ) and a group with low BRS (DMBRS↓ ). Values presented are median (inter-quartile range). Results: Preoperative vs intraoperative BRS was 6.2 (4.5–8.5) vs 1.9 (1.1–2.5, P <0.001) ms mm Hg −1 for controls, 5.8 (4.9–7.6) vs 2.7 (1.5–3.9, P <0.001) ms mm Hg −1 for patients with DMBRS↑, and 1.9 (1.5–2.8) vs 1.1 (0.6–2.5, P =0.31) ms mm Hg −1 for patients with DMBRS↓ . Preoperative vs intraoperative CA efficacy was 43° (38–46) vs 43° (38–51, P =0.30), 44° (36–49) vs 41° (32–49, P =0.52), and 34° (28–40) vs 30° (27–38, P =0.64) for controls, DMBRS↑, and DMBRS↓ patients, respectively. Conclusions: In diabetic patients with low preoperative BRS, preoperative CA efficacy was also impaired. In controls and diabetic patients, CA was unaffected by sevoflurane-based anaesthesia. We therefore conclude that sevoflurane-based anaesthesia does not contribute to a 'double-hit' phenomenon on cerebral perfusion. Clinical trial registration: NCT 03071432 .